Checklist of the “true” slime molds (Eumycetozoa, Amoebozoa) from Tlaxcala, Mexico - Hernández, Berlia Beneric Salazar; Guerrero, Fabian Rojas; Montes, José Rubén; Alvarado, Carlos Rojas; Torres, Arturo Estrada (Phytotaxa, 2026)
Eumycetozoa, in its present circumscription, is made up of three closely related groups of Amoebozoa that form sporocarps during their life cycle: Ceratiomyxomycetes, Dictyosteliomyxomycetes, and Myxomycetes. In Mexico, and particularly in the state of Tlaxcala, Myxomycetes is a relatively well studied group, while Ceratiomyxomycetes and Dictyosteliomycetes have barely been considered in biodiversity studies. However, the discovery of new species, the exploration of new areas in the state and recent changes in nomenclature and classification system based on molecular evidence make necessary to update the list of species found in the state. This paper presents a list of new encounters made by the authors, as well as all previous records published between 1976 and 2024, updating the nomenclature in accordance with current proposals and including comments on morphology, ecology or nomenclature when this was considered relevant. A total of 251 species of Eumycetozoans are reported in the state, with 13 new records for the Neotropics, nine for Mexico and 27 for Tlaxcala. Emphasis is placed on the need to study underexplored environments, in addition to conducting studies that clarify the identity of species that comprise species complexes difficult to define with morphological evidence alone.